Towards the Ecotourism Development: Opportunities and Challenges in Delft Island, Jaffna District- Sri Lanka: Ke arah Pembangunan Ekopelancongan: Peluang dan Cabaran di Pulau Delft, Daerah Jaffna, Sri Lanka - Piratheepa, Vipulan; Chan, Ngai Weng; Suriati, Ghazali (GEOGRAFI, 2021)
Delft Island is one of the seven inhabited Islands of the Jaffna Peninsula. It has been prioritized for ecotourism development after the postwar scenario. Delft Island has unique features to promote ecotourism. However, there are several challenges faced by the relevant authorities during the development process. This study explores to identify the opportunities and challenges in the context of ecotourism development. In-depth semi-structured interviews among the executive level of a government officer, focus group discussions from the community-based organization, and field visits have been carried out to collect primary data. Thematic and qualitative descriptive analysis methods have been used to analyze the data. The result reveals that the government policies, physical and biological features, history, culture and income generation as the opportunities and administrative mechanism, while shortcoming of environmental conservation, improper usage of resources, lack of community awareness, and infrastructure facilities as challenges. This study suggests that, while preparing an integrated plan for ecotourism development, a proper planning process should be adopted with interdepartmental coordination. The intensive training programme should be arranged to involve the local community because ecotourism development is novel to the societies living in this area. Thus, Delft can be promoted as an eco-friendly Tourism Island through concerted effort among all stakeholders.